Presence of host and bacterial-derived collagenolytic proteases in carious dentin: a systematic review of ex vivo studies - Barbosa, Cecília de Brito; Monici Silva, Isabela; Cena, Jéssica Alves de; Stefani, Cristine Miron; Dame-Teixeira, Naile (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction and aim The presence of host collagenases in the degradation of the protein matrix at later stages of carious dentin lesions development, as well as the potential involvement of bacterial collagenases, have been suggested but lack conclusive evidence. This study aims to conduct a systematic review to comprehensively assess the profile of host and bacterial-derived collagenolytic proteases in both root and coronal dentin carious lesions. Methods The search was performed in eight databases and the grey literature. Studies evaluating ex vivo dentin, extracted teeth, or biofilms from natural caries lesions were included. The methodological quality of studies was assessed using the Joanna Briggs Institute tool. Synthesis of the results and the certainty of evidence were performed following the Synthesis without Meta-analysis (SWiM) checklist and GRADE approach for narrative synthesis, respectively. Results From 935 recovered articles, 18 were included. Although the evidence was very uncertain, it was possible to suggest that 1) MMP-2, MMP-9, MMP-13, and CT-B may be increased in carious dentin when compared to sound dentin; 2) there is no difference in MMP-2 presence, while MMP-13 may be increased in root when compared to coronal carious dentin; 3) there is no difference of MMP-2 and MMP-9 expression/activity before and after cavity sealing; 4) MMP-8 may be increased in the dentin before cavity sealing compared to dentin after cavity sealing; 5) there is no difference of MMP-20 in irradiated vs. non-irradiated carious dentin. MMP-20 probably reduces in carious outer dentin when compared to carious inner dentin (moderate certainty). Genes encoding bacterial collagenolytic proteases and protein-degrading bacteria were detected in coronal and root carious lesions. Conclusion Trends in the direction of the effect were observed for some collagenolytic proteases in carious dentin, which may represent a potential target for the development of new treatments. (Protocol register-PROSPERO: CRD42020213141).